INTERNATIONAL ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS IN THE ASIAN PART OF RUSSIA - Alisa V. Melikyan (Высшее образование в России)
The article presents the results of a quantitative analysis of the international activities of universities and universities' branches in the Asian part of Russia on the basis of the indicators of the monitoring of universities' effectiveness conducted in 2015. The results of the international activity of 322 universities and universities' branches were analyzed on the basis of the following indicators: the number of foreign students who studied at the main programs, the number of Russian and foreign students who participated in short-term international mobility programs; the number of international double degree programs and the number of students at these programs; the number of foreign graduate students; the number of foreign researchers and teachers; revenues of higher education institutions from the educational activities and from R & D obtained from foreign sources; the number of articles produced in collaboration with foreign organizations. According to the study, the best results demonstrate the major state universities and the universities with special status. In other higher education institutions some international activities are realized with varying degrees of success. Organizations of higher education in Tomsk, Omsk, Novosibirsk and Sverdlovsk regions demonstrate the highest values according to the analyzed indicators. In general, higher education institutions of the Siberian Federal District have the highest results compared to the results of institutions from the other two federal districts. Foreign students studied in 85.7% of higher education institutions in the region. In universities and branches of the region incoming and outgoing programs of academic mobility were realized and 2463 foreign and 2110 Russian students participated in them. In the institutions of the region there are 295 international double degree programs and 2850 students studied at them. The region has trained 630 foreign postgraduate students, 394 foreign faculty members worked in the region. Faculty of universities and branches of the region published 3772 articles prepared in collaboration with the faculty form foreign organizations. Organizations of higher education in the region have received 1218.5 million rubles of the income from educational and scientific activity from foreign sources.